MADS1, a novel MADS-box protein, is involved in the response of Nicotiana benthamiana to bacterial harpin(Xoo) - Zhang, Huajian (Journal of experimental botany, 2016)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.